GAME EDUKASI ADAPTIVE LEARNING UNTUK MENINGKATKAN MINAT BELAJAR PEMROGRAMAN C++ BAGI MAHASISWA - Hudzaifah Nabil Amrullah; Adhi Rizal; Aji Primajaya (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
C++ programming is a fundamental course in computer science education; however, its abstract nature and strict syntax lead to low student learning interest. Previous studies indicate that conventional learning approaches are one-size-fits-all and do not accommodate individual learning style differences. This study designs and implements an adaptive learning-based educational game called